2021
DOI: 10.18805/lr-635
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Biochemical Composition and Pigment Content in Legume and Cereal Microgreens

Abstract: Background: Legumes and cereals microgreens are consumed both in healthy nutrition and as a natural food against many degenerative diseases due to their rich bioactive content. The research was carried out to determine the biochemical contents of 5 legumes and 7 cereals. Methods: The research was conducted in Van Yuzuncu Yıl University Field Crops Department Laboratory in 2020, in a controlled growing environment, according to the completely randomized experimental design. Total antioxidant activity, total phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Similarly, in the 6-day old lentil sprouts, nearly similar TPC (19.4 mg/g DW) was reported by Swieca et al [ 52 ]. Furthermore, in the lentil seeds, Fouad et al [ 53 ] and Altuner [ 54 ] reported TPC to the tune of 1510.10 and 385.44 mg/100 g DW, respectively. A similar range of TPC was also reported for mustard (1889.76 mg/100 g FW) and radish (211.19 mg/100 g FW) seedlings [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the 6-day old lentil sprouts, nearly similar TPC (19.4 mg/g DW) was reported by Swieca et al [ 52 ]. Furthermore, in the lentil seeds, Fouad et al [ 53 ] and Altuner [ 54 ] reported TPC to the tune of 1510.10 and 385.44 mg/100 g DW, respectively. A similar range of TPC was also reported for mustard (1889.76 mg/100 g FW) and radish (211.19 mg/100 g FW) seedlings [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was concluded that total phenolic contents (TPC) was considerable good in red clover (46%) and maize (73%) as compared to cowpea and other studied legumes ( Altuner et al, 2022 ). Although, biochemical parameters have not been correlated in legumes but pigment parameters were positively associated in legumes and cereals ( Altuner, 2021 ). Further, positive correlation was found for total antioxidant activity, total phenolic content and total ascorbic acid in cereals ( Altuner, 2021 ).…”
Section: Strategies To Overcome Limitations Of Microgreen Productionmentioning
confidence: 99%
“…Although, biochemical parameters have not been correlated in legumes but pigment parameters were positively associated in legumes and cereals ( Altuner, 2021 ). Further, positive correlation was found for total antioxidant activity, total phenolic content and total ascorbic acid in cereals ( Altuner, 2021 ).…”
Section: Strategies To Overcome Limitations Of Microgreen Productionmentioning
confidence: 99%